2020
DOI: 10.1002/rth2.12261
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of oral anticoagulant treatment for atrial fibrillation in the Netherlands: A surveillance study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: In contrast to vitamin K antagonists (VKA), direct oral anticoagulants (DOAC's) are not strictly monitored and dose titrated by anticoagulation clinics in the Netherlands. This may affect drug persistence of atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 46 publications
2
44
0
1
Order By: Relevance
“…As was recently published by Zielinksi et al, the mean age of oral anticoagulant naïve patients (n = 70 977) in SFK was 70 years (SD, 11), 38 995 were male (55%), and 60 028 used comedication (85%). For patients in SFK who switched from VKA to DOAC (n = 6356) the mean age was 70 years (SD, 11), 3667 were male (58%), and 6323 used comedication (99%) (Table ).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…As was recently published by Zielinksi et al, the mean age of oral anticoagulant naïve patients (n = 70 977) in SFK was 70 years (SD, 11), 38 995 were male (55%), and 60 028 used comedication (85%). For patients in SFK who switched from VKA to DOAC (n = 6356) the mean age was 70 years (SD, 11), 3667 were male (58%), and 6323 used comedication (99%) (Table ).…”
Section: Resultsmentioning
confidence: 62%
“…For patients in SFK who switched from VKA to DOAC (n = 6356) the mean age was 70 years (SD, 11), 3667 were male (58%), and 6323 used comedication (99%) (Table ). In SFK data, persistence rates among patients with atrial fibrillation after 1 year of follow‐up was 77% for patients who switched from a VKA to a DOAC, while in the Monitoring of direct oral anti‐coagulant (MONDOAC) study the persistence rate was 94% for patients with atrial fibrillation (Table ) . In SFK data, the adherence rate for DOAC after 1 year of follow‐up was 88% for patients who switched from a VKA to a DOAC, this was also 88% for patients with atrial fibrillation in the MONDOAC study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 A Dutch study recently found that 34% of patients with newly diagnosed AF had stopped treatment with nonvitamin K antagonists after one year, with female sex being associated with a higher risk of nonadherence. 40 In summary, women are more likely than men to receive suboptimal anticoagulation, a difference not likely to be explained be differences in bleeding risk profiles. If the Sc Fig.…”
Section: Potential Clinical Consequences Of Changing the Risk Scorementioning
confidence: 99%
“…Based on a 1 year non-persistence in one-third of the NOAC users, 1815 patients on NOACs will be non-persistent. 36 If we assume a 50% increased risk of ischaemic stroke/systemic embolism in these patients, we can expect on average a 3% yearly risk compared with the 2% in the 3685 patients who will continue to use their drug. 7 During 2-year follow-up, we expect 250 patients will develop ischaemic stroke/systemic embolism.…”
Section: Methodsmentioning
confidence: 99%